Immunobiology :The Immune System in Health and Disease - Janeway, Charles Travers, Paul Walport, Mark (Garland Science, 2005)
Summarizing the basic immunological concepts, this textbook looks at the main aspects of adaptive immunity, then integrates all the preceding material at the level of the complete organism in both health and disease.